2007
DOI: 10.1002/0471143030.cb1512s36
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Regulated Secretion Using PC12 Cells

Abstract: The catecholamine‐secreting PC12 cell line derived from the rat adrenal medulla has long been considered a model system for neurosecretion and neuronal differentiation. PC12 cells contain a large number of secretory granules (otherwise known as large dense‐core vesicles) for storage of small molecules, processing enzymes, neuropeptides, and peptide hormones. Secretory granule exocytosis in PC12 cells is tightly regulated by calcium and occurs in response to a secretagogue. This unit provides protocols for main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…This, in fact, suggested that H 3 Rs may influence neuronal AT 1 R expression in hearts subjected to I/R. Inasmuch as cardiac synaptosomes probably include cholinergic, purinergic, and sensory C-fiber terminals (Seyedi et al, 1999;Morrey et al, 2010), we tested whether H 3 R activation would influence AT 1 R expression in PC12-H 3 cells, which once differentiated with NGF express a typical sympathetic neuron phenotype (Taupenot, 2007;Morrey et al, 2008;Corti et al, 2011). Indeed, we found that activation of H 3 R with imetit markedly diminished AT 1 R protein abundance in these cells, an action that was abolished by the H 3 R antagonist clobenpropit.…”
Section: Discussionmentioning
confidence: 99%
“…This, in fact, suggested that H 3 Rs may influence neuronal AT 1 R expression in hearts subjected to I/R. Inasmuch as cardiac synaptosomes probably include cholinergic, purinergic, and sensory C-fiber terminals (Seyedi et al, 1999;Morrey et al, 2010), we tested whether H 3 R activation would influence AT 1 R expression in PC12-H 3 cells, which once differentiated with NGF express a typical sympathetic neuron phenotype (Taupenot, 2007;Morrey et al, 2008;Corti et al, 2011). Indeed, we found that activation of H 3 R with imetit markedly diminished AT 1 R protein abundance in these cells, an action that was abolished by the H 3 R antagonist clobenpropit.…”
Section: Discussionmentioning
confidence: 99%
“…After preincubation, cells were incubated for 3 h in the same medium ("3 h basal") followed by 15-min incubations without ("ϪK") and with ("ϩK") 55 mM KCl to stimulate granule exocytosis (35). Cells were quickly rinsed in Hanks' buffered salt solution between incubations.…”
Section: Methodsmentioning
confidence: 99%
“…In our investigation, we used the PC12 rat pheochromocytoma cell line, which acquires a sympathetic nerve phenotype when treated with NGF (Dichter et al, 1977;Taupenot, 2007). Having stably transfected PC12 cells with human H 3 R, a PTX-sensitive G i/o -coupled receptor (see Figs.…”
Section: Discussionmentioning
confidence: 99%
“…To accomplish this, we evaluated the effects of H 3 R activation on I Ca and endogenous transmitter exocytosis in nerve-growth factor (NGF)-differentiated rat pheochromocytoma cells (PC12) stably transfected with H 3 R and the G␤␥ scavenger ␤-adrenergic receptor kinase 1 (␤-ARK1)-(495-689)-polypeptide (Koch et al, 1994;Dickenson and Hill, 1998). NGF-differentiated PC12 cells were chosen as a functional model of sympathetic neurotransmission because their phenotype closely resembles that of sympathetic neurons (Dichter et al, 1977;Taupenot, 2007). Our results demonstrate a pivotal involvement of the G␤␥ subunit in H 3 R-mediated attenuation of neuronal I Ca and consequent neurotransmitter exocytosis.…”
mentioning
confidence: 99%